The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1007/bf00044885
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of reproduction, dispersion, and competition in river plants: A review

Abstract: The present paper reviews the literature on reproduction, survival, dispersion and competition in aquatic plants of mostly European rivers. The specificity of the strategies of colonization in aquatic plants in comparison with terrestrial plants is noted. The importance of the knowledge of these life history traits in the control of the harmful effects caused by aquatic plants and for ecosystem management is also considered. The difficulty of applying current ecological theories concerning adaptative strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
165
1
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(180 citation statements)
references
References 188 publications
6
165
1
5
Order By: Relevance
“…Ceratophyllum demersum has a suitable morphology for light interception and longevity (GRIME 1979). These results suggest that C. demersum and M. spicatum are stress-tolerant, which are in line with other researches (FRANK 1975, SEGRETAIN 1996.…”
Section: Discussionsupporting
confidence: 92%
“…Ceratophyllum demersum has a suitable morphology for light interception and longevity (GRIME 1979). These results suggest that C. demersum and M. spicatum are stress-tolerant, which are in line with other researches (FRANK 1975, SEGRETAIN 1996.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, they reported no difference in associated hydrophyte and helophyte species between R. fluitans and R. penicillatus. Previous studies have indicated that the high levels of vegetative reproduction observed in many populations of Ranunculus subgenus Batrachium species are associated with polyploidy and/or the formation of hybrids (Cook 1966;Holmes 1980;Dahlgren 1993;Barrat-Segretain 1996). Although hybrids between R. fluitans and R. penicillatus have been reported previously from the Six Mile Water (Hackney 1992), only a single potential case of hybridization was identified in the present study.…”
Section: Ranunculus Fluitans In Ireland Is Restricted To the Six Milecontrasting
confidence: 54%
“…It was first identified in 1865 and has been recorded only in the same section of the river since then (Beesley 2006). R. fluitans is monoecious, and subaquatic pollination occurs as a result of the formation of an air bubble in the perianth (Arber 1920), although it has been suggested that vegetative reproduction may be more common (Zander and Wiegleb 1987;Cook 1990;Barrat-Segretain 1996). The species is occasionally found growing with R. penicillatus (Stream water crowfoot) and, although morphological differentiation between the two can be difficult, there are anecdotal reports of sterile hybrids between the species occurring in the sole Irish population (Hackney 1992).…”
Section: Ranunculus Fluitans Lam (River Water Crowfoot) Is a Subaquamentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of vegetative propagules is diverse, but usually, any plant fragment that disperses and is capable of resprouting when it meets a favourable habitat after dispersal is considered to be a vegetative propagule (Barrat-Segretain, 1996). Vegetative propagules can be rhizomes, stolons, tubers, turions, simple stem or leaf fragments or even entire plants.…”
Section: Introductionmentioning
confidence: 99%